The Role of State Authority in Ensuring Political Stability (Eurasian Journal of Humanities and Social Sciences, 2022)
The article discusses the features and mechanisms for ensuring and maintaining sociopolitical stability in Uzbekistan. The scientific theoretical foundations in the study of this phenomenon, developed by domestic and foreign scientists, are analyzed. Political stability in the new Uzbekistan is understood as an indispensable condition for effective socio-economic development. The article studies the appeal of the leadership of Uzbekistan of various generations to the tools for establishing socio-political stability as a way to implement the modernization course program. It was found that maintaining the political stability of society in modern Uzbekistan becomes possible through the harmonization of social relations, flexible national policy, economic growth and the use of ideological instruments in the public administration system. The author has studied the main mechanisms for the development of the stability of the political system of Uzbekistan at the present stage. It is concluded that the stable political development of modern Uzbekistan contributes to strengthening the people's trust in political power